The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s11920-015-0569-x
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmology Issues in Schizophrenia

Abstract: Schizophrenia is a complex mental disorder associated with not only cognitive dysfunctions, such as memory and attention deficits, but also changes in basic sensory processing. Although most studies on schizophrenia have focused on disturbances in higher-order brain functions associated with the prefrontal cortex or frontal cortex, recent investigations have also reported abnormalities in low-level sensory processes, such as the visual system. At very early stages of the disease, schizophrenia patients frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 104 publications
(121 reference statements)
1
19
0
Order By: Relevance
“…The review by Gracitelli et al (2015) showed that most studies on schizophrenia have focused on disturbances in higher-order brain functions associated with the frontal and pre-frontal cortex. However, recently there have been reported abnormalities in low-level sensory processes, such as the visual system.…”
Section: Schizophrenia In Ophthalmologymentioning
confidence: 99%
See 3 more Smart Citations
“…The review by Gracitelli et al (2015) showed that most studies on schizophrenia have focused on disturbances in higher-order brain functions associated with the frontal and pre-frontal cortex. However, recently there have been reported abnormalities in low-level sensory processes, such as the visual system.…”
Section: Schizophrenia In Ophthalmologymentioning
confidence: 99%
“…It is the variations in the dopamine and glutamate systems that have been highlighted in the pathophysiology of the disease. Also, the loss of retinal nerve fiber layer thickness has been well established in several neurologic diseases which also involve dopamine and glutamate dysregulation (9). Thirty schizophrenia patients and 30 agematched controls were studied with spectral-domain optical coherence tomography and it was found that these measurements were reduced in schizophrenia patients.…”
Section: Schizophrenia In Ophthalmologymentioning
confidence: 99%
See 2 more Smart Citations
“…This suggestion is supported by recent reviews. 4,5 This article will review selected structural and functional eye abnormalities found in schizophrenia and other psychiatric disorders. It will then examine some infections of the eye and central nervous system to demonstrate how such infections might account for the eye abnormalities.…”
Section: Introductionmentioning
confidence: 99%